The moderating effect of perceived hope in the relationship between anxiety and posttraumatic growth during the Russian-Ukrainian war - Slezackova, Alena; Malatincova, Tatiana; Millova, Katarina; Svetlak, Miroslav; Krafft, Andreas M. (Frontiers in Psychology, 2024)
This study examines the relationships between perceived hope, posttraumatic growth, well-being, anxiety, and perceived threat of the Russian-Ukrainian War (RUW) in the Czech adult population. Drawing on the evidence of posttraumatic growth (PTG) amidst crisis, we hypothesized that perceived hope moderates the effects of perceived threat of war and anxiety on PTG. Data were obtained from 1,000 Czech respondents via an online questionnaire ten months post-invasion. The form included measures of posttraumatic growth, perceived hope, well-being, anxiety and depression, and perceived threat of war. Our findings reveal that perceived hope acted as a moderator enhancing the positive effects of perceived threat and anxiety on PTG. However, perceived hope did not significantly moderate the direct effects of perceived threats and anxiety on well-being. This study highlights the significant role of hope amidst adversity and underscores its potential as a target for interventions aiming to foster PTG in populations who navigate traumatic experiences. Furthermore, it advocates for continued exploration of the factors interacting to enhance well-being and facilitate PTG in affected communities.